Traditional Medicine and Biomedicine among Mapuche Communities in Temuco, Chile: New Forms of Medical Pluralism in Health Care Delivery - Costanza Torri, Maria; Laplante, Julie (Anthropologica, 2013)
Within Mapuche indigenous communities in Temuco, Araucania Region, Chile, traditional healers (machi) and their healing practices are part of everyday life for many people. This article shows that there is a clear tendency for Mapuche people to combine different therapeutic approaches to solve their health problems. We argue, however, that this behaviour is not explained by a crisis of identity among the urban Mapuche community in which the person has lost his or her own indigenous cultural scheme but has not fully assimilated the Westernized model. This article shows that this form of therapeutic pluralism by urban Mapuche is motivated by the adoption of a holistic perception of health and of plural medicinal practices among these indigenous communities.